Nadia - Krogmann, C. W. (Carrie Williams), -1943 (B. F. Wood Music Co., 1912)
Sheet music for piano for "Nadia, Opus 91, No. 3" by C. W. Krogmann. Part of the "5 Souvenirs du Bal pour Pianoforte" par C. W. Krogmann.